QoSPY an approach for QoS monitoring in diffserv networks. - Ricardo de Farias Santos (2001)
Emerging applications with strict performance requirements have introduced needs for distinguishing services in computer networks so as to prioritize some applications more important or profitable than others. Actually it is possible to deliver only one service for all kinds of traffic so far, known as Best-effort service. Therefore, some Quality of Service (QoS) models were developed. These models have been used for resource allocation within network elements so that network traffic can be classified or differentiated. This has allowed a better network resources utilization. Nevertheless, it is not sufficient just to allocate resources for applications. We also need to monitor QoS parameters, in order to attest if the desired QoS is the one being provided, since problems with network element frequently happen. Some QoS monitoring tools were already developed, but they are able to detect End-to-end service degradations only. Hence they cannot pinpoint the sources of degradations. This research work proposes the development of QoS$_{PY}$, a SNMP-based distributed monitoring application that uses information from network elements (e.g. routers) to assess QoS. The major contribution of this work is to perform intermediate monitoring to provide means of detecting and locating QoS degradations into the network. In order to verify this contribution, a prototype was deployed and tested with experimental testbeds.